Betty Boop News. - Heuten, Ingrid; Mils, Greet (Antwerpen : Vrouwencafé Betty Boop, 1984)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijksRedactie : Vrijdagmarkt 5, 2000 AntwerpenV.V. De Chatteraar
Nederlands
Periodiek
Keywords: vrouwencafé